nv-Lindelöfness - Abuage, Mariam M.; Kilicman, Adem; Sarsak, Mohammad Shawqi Omar (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
Our work aims to study nearly ν-Lindelöf (briefly. nν-Lindelöf) space in generalized topological spaces. Moreover, some mappings and decompositions of continuity are studied. The main result that we obtained on is the effect of (δ,δ’)-continuous function on nν-Lindelöf space.